Enhanced graphitic domains of unreduced graphene oxide and the interplay of hydration behaviour and catalytic activity. (November 2021) - Foller, Tobias; Daiyan, Rahman; Jin, Xiaoheng; Leverett, Joshua; Kim, Hangyel; Webster, Richard; Yap, Jeaniffer E.; Wen, Xinyue; Rawal, Aditya; De Silva, K. Kanishka H.; Yoshimura, Masamichi; Bustamante, Heriberto; et al.
Graphical abstract: Abstract: Previous studies indicate that the properties of graphene oxide (GO) can be significantly improved by enhancing its graphitic domain size through thermal diffusion and clustering of functional groups. Remarkably, this transition takes place below the decomposition temperature of the functional groups and thus allows fine tuning of graphitic domains without compromising with the functionality of GO. By studying the transformation of GO under mild thermal treatment, we directly observe this size enhancement of graphitic domains from originally ≤40 nm 2 to >200 nm 2 through an extensive transmission electron microscopy (TEM) study. Additionally, we confirm the integrity of the functional groups during this process by a comprehensive chemical analysis. A closer look into the process confirms the theoretical predicted relevance for the room temperature stability of GO and the development of the composition of functional groups is explained with reaction pathways from theoretical calculations. We further investigate the influence of enlarged graphitic domains on the hydration behaviour of GO and the catalytic performance of single atom catalysts supported by GO. Additionally, we show that the sheet resistance of GO is reduced by several orders of magnitude during the mild thermal annealing process.